Implementation of Web-Based Student Management Information System in SDI Taman An-Nahl Sidoarjo - Rizka Hadiwiyanti; Anindo Saka Fitri; Tri Lathif Mardi Suryanto; Erlin Ayu Khrisnawati; Ferry Kurniawan (Nusantara Science and Technology Proceedings, 2022)
SDI Taman An-Nahl Sidoarjo is an educational institution that plays an active role in developing the potential of students. However, in this digitalization era, there are limitations in accelerating performance in managing student data so that it has the impact of not having a database for students, not having a database of student scores, and not reporting student activities to parents. This situation is due to the fact that an integrated management information system (MIS) has not been implemented. The focus of this research is to develop a web-based Student Management Information System that can help teachers manage student learning outcomes data and help parents monitor the progress of their children's learning outcomes. The development of this system has a scope consisting of valid student data and student identification numbers, monitoring of student activities, and reporting of student activities to parents. The system test results show that the system can run well, although there are minor errors. The implementation of the Student Management Information System has been successfully carried out, so that users can access the system in real time through the website.